A novel and efficient method for resources recycling in waste photovoltaic panels: High voltage pulse crushing. (1st June 2020) - Zhao, Pengfei; Guo, Junwei; Yan, Guanghui; Zhu, Guangqing; Zhu, Xiangnan; Zhang, Zhenxing; Zhang, Bo
Abstract: Photovoltaic power generation technology has developed rapidly in the past decade due to its clean and efficient characteristics. However, with the development of photovoltaic power generation technology, a large number of waste photovoltaic panels are generated, but there is no clean and effective method for resources recycling in waste photovoltaic panels. High-voltage pulsing tends to cause fractures at interfaces of materials with different dielectric constants, which has a satisfactory recovery effect on layered materials like photovoltaic panels In this paper, high voltage pulse crushing is used to dissociate and enrich waste photovoltaic panels, the experimental results show that there are differences in the selectivity of different components during high-voltage pulse crushing (selectivity: Ag > Si > glass). This makes high voltage pulse crushing have good enrichment effect on photovoltaic panels. Most of the high-value elements are enriched to lower grain size, the glass purity of 0.5∼4 mm grain size can be directly recycled while it reaches over 98%. High-voltage pulse crushing has the most obvious enrichment effect on silver, Selectivity increases with the decrease of field strength and pulse number. The enrichment rate of silver in the lower field strength and pulse can reach 3.08, and the recovery rate is 54.07%. As the field strength and pulse number increase, the enrichment rate of silver drops to 1.67 but the recovery rate increases to 89.41%. The silver recovery can be effectively improved by adjusting the electrode gap. High-voltage pulse crushing can effectively enrich and recover the silver in the waste photovoltaic panels, providing convenience for subsequent sorting. Graphical abstract: Image 1 Highlights: The particle size enrichment effect was found when the photovoltaic panel was broken by high voltage pulse. The stripping sequence of photovoltaic panel components during high voltage pulse crushing was investigated. The Silver in photovoltaic panels can be effectively enriched and recovered by high voltage pulse crushing. The recovery effect of silver on breaking photovoltaic panels with high voltage pulse was studied systematically.